If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.5 + -2y = 2.5 + -0.5y Solving 5.5 + -2y = 2.5 + -0.5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '0.5y' to each side of the equation. 5.5 + -2y + 0.5y = 2.5 + -0.5y + 0.5y Combine like terms: -2y + 0.5y = -1.5y 5.5 + -1.5y = 2.5 + -0.5y + 0.5y Combine like terms: -0.5y + 0.5y = 0.0 5.5 + -1.5y = 2.5 + 0.0 5.5 + -1.5y = 2.5 Add '-5.5' to each side of the equation. 5.5 + -5.5 + -1.5y = 2.5 + -5.5 Combine like terms: 5.5 + -5.5 = 0.0 0.0 + -1.5y = 2.5 + -5.5 -1.5y = 2.5 + -5.5 Combine like terms: 2.5 + -5.5 = -3 -1.5y = -3 Divide each side by '-1.5'. y = 2 Simplifying y = 2
| 720=-0.5x^2+50x-472 | | 3(4n-1)=45 | | 32+102+x+25=180 | | x^2+y^2-10+6y+27=0 | | 8a+25+7=0 | | 12t=48 | | 36x+16+3=15 | | x^2=63 | | 2r=68 | | -10n+18=-8n-10 | | 355x+2+159x=459-x | | 2x+4=150 | | 7c=56 | | 22-x=3(x+2) | | 75x^10-3x^8=0 | | -X^2-3=0 | | -x+4x-7=3-4x | | X^3-3=0 | | 5-(x+3)=20 | | 6x+2+8=16 | | -7c+6=-22 | | 3x(2x+5)+6x= | | -X^3-3x=0 | | 6(x+8)-2(x-4)=1 | | 4(-4+4x)=-64 | | (5x+6)(3x^2-7x+2)=0 | | 4x+2(x)=8 | | -4(4+2x)=-48 | | x+2(x-1)=3(x-3) | | -4(4v-4)=80 | | 4(1+4n)=68 | | 5x=2.5 |